Wettability control of polymeric microstructures replicated from laser-patterned stamps - Fu, Yangxi; Soldera, Marcos; Wang, Wei; Milles, Stephan; Deng, Kangfa; Voisiat, Bogdan; Nielsch, Kornelius; Fabian Lasagni, Andres (Scientific Reports, 2020)
In this study, two-step approaches to fabricate periodic microstructures on polyethylene terephthalate (PET) and poly(methyl methacrylate) (PMMA) substrates are presented to control the wettability of polymeric surfaces. Micropillar arrays with periods between 1.6 and 4.6 µm are patterned by plate-to-plate hot embossing using chromium stamps structured by four-beam Direct Laser Interference Patterning (DLIP). By varying the laser parameters, the shape, spatial period, and structure height of the laser-induced topography on Cr stamps are controlled. After that, the wettability properties, namely the static, advancing/receding contact angles (CAs), and contact angle hysteresis were characterized on the patterned PET and PMMA surfaces. The results indicate that the micropillar arrays induced a hydrophobic state in both polymers with CAs up to 140° in the case of PET, without modifying the surface chemistry. However, the structured surfaces show high adhesion to water, as the droplets stick to the surfaces and do not roll down even upon turning the substrates upside down. To investigate the wetting state on the structured polymers, theoretical CAs predicted by Wenzel and Cassie-Baxter models for selected structured samples with different topographical characteristics are also calculated and compared with the experimental data.
CRIS-Team Scopus Importer:2022-04-14